Beyond Cognitive Framing Processes: Anger Mediates the Effects of Responsibility Framing on the Preference for Punitive Measures. (20th March 2015) - Kühne, Rinaldo; Weber, Patrick; Sommer, Katharina
<x xml:space="preserve">Abstract</x> A new stream of research indicates that framing effects are based on emotional as well as cognitive processes. However, it is not entirely clear whether emotions mediate framing effects and what the moderators of emotional mediation processes are. To address these questions, we conducted an experiment in which the framing of responsibility for a social problem was manipulated (ambivalent vs. high‐responsibility frame). We find that the high‐responsibility frame increased the preference for punitive measures by increasing responsibility beliefs and eliciting anger. Furthermore, we find that trait anger moderates the framing effect on anger and that responsibility beliefs are positively associated with anger intensity. The significance of these findings for framing research and suggestions for future studies are discussed.